Better perceived health among the Swedish-speaking minority as compared with the Finnish-speaking majority in Finland : a cross-sectional study with an intergenerational perspective - Suominen, Sakari; Stark Ekman, Diana; Saarela, Jan; Volanen, Salla-Maarit; Stenlund, Säde; Sillanmäki, Lauri; Sumanen, Markku (Sage, 2025)
Background: Previous research has shown that the Swedish speaking minority in Finland has slightly but significantly better health compared with the Finnish speaking majority. However, a clear explanation for this is lacking.
Aim: The aim of the study was to explore differences of perceived health comparing three groups: Swedish speakers with reported dominance of Swedish also in the preceding generation; contemporary Finnish speakers with reported dominance of Finnish in the preceding generation and a group with a reported mixed-language structure of Finnish and Swedish between generations.
Individuals and methods: Health and Social Support is an on-going population-based survey initiated in 1998 (N = 64,797), aimed at working-age adults. The present study is based on the 2012 follow-up survey, which included a question on the dominating language (Swedish or Finnish) of the respondents and their parents. The outcome was perceived health, which in this study was dichotomized to very good/good and intermediate/poor/very poor. The statistical analysis was carried with logistic regression, using SAS software. Age, gender and occupational training were included as covariates in the multivariable analysis.
Results: This study found that the Swedish-speaking group in Finland report better perceived health compared with the Finnish-speaking group (odds ratio 1.28, 95% confidence interval 1.04-1.57, p < 0.001). The health of the mixed language-speaking group fell between the other two groups.
Conclusions: The results gave some support to a culturally mediated mechanism for the health advantage of Swedish speakers. Cultural features of Swedish-speaking groups in Finland may also support health promotion of the Finnish-speaking majority.